1995
DOI: 10.1016/0378-8741(95)90037-3
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral screening of British Columbian medicinal plants

Abstract: One hundred methanolic plant extracts were screened for antiviral activity against seven viruses. Twelve extracts were found to have antiviral activity at the non-cytotoxic concentrations tested. The extracts of Rosa nutkana and Amelanchier alnifolia, both members of the Rosaceae, were very active against an enteric coronavirus. A root extract of another member of the Rosaceae, Potentilla arguta, completely inhibited respiratory syncytial virus. A Sambucus racemosa branch tip extract was also very active again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(82 citation statements)
references
References 15 publications
(31 reference statements)
1
78
1
2
Order By: Relevance
“…S. nigra extracts are also characterized by a high content of antiviral flavonoid anthocyanins [42]. Additionally, the antiviral compound quercetin is largely present in both S. nigra and in Amelanchier alnifolia (Saskatoon serviceberry) [43], a known inhibitor of the bovine coronavirus, in vitro [44]. Combined, these studies suggested that extracts of R. rosea, N. sativa, and S. nigra might possess broad antimicrobial or antiviral properties.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…S. nigra extracts are also characterized by a high content of antiviral flavonoid anthocyanins [42]. Additionally, the antiviral compound quercetin is largely present in both S. nigra and in Amelanchier alnifolia (Saskatoon serviceberry) [43], a known inhibitor of the bovine coronavirus, in vitro [44]. Combined, these studies suggested that extracts of R. rosea, N. sativa, and S. nigra might possess broad antimicrobial or antiviral properties.…”
Section: Introductionmentioning
confidence: 81%
“…For example, extracts from A. alnifolia berries, branches, and leaves have chemicals (3-carreolyquinic acid and cyanidin 3-glucoside) that are found in S. nigra but not in R. rosea or N. sativa [42,71,73]. And indeed, A. alnifolia branch extracts inhibited the bovine coronavirus in vitro [44]. Finally, a currently unidentified chemical or combination of chemicals may be responsible for the ability of S. nigra extract to compromise IBV virion structure.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that V. thapsus has antiviral activity against influenza in chicken embryos (21). In a previous study, leaf extracts of this plant have been shown to be active against bovine herpes virus type 1, and showed slight antibacterial and antifungal activity (22)(23)(24). Methanol extract has been shown to be effective against mosquito larvae (25).…”
Section: Methodsmentioning
confidence: 99%
“…The antiviral and anti-tumor activity shown by Trichomanes reniforme is due to the presence of mangiferin, which can kill cancer cells and has anti-HIV effects (Guha et al, 1996). The antiviral activity of Pteris glycyrrhiza (McCutcheon et al, 1995), P. vulgare, and Polypodium aureum (Husson et al, 1986) has been documented. A new antiviral compound, woodorien, was derived and identified by Xu et al (1993).…”
Section: Anti-cancer Antidiabetic and Antiviral Activitymentioning
confidence: 99%
“…(Basile et al, 1997), Adiantum lunulatum (Reddy et al, 2001), E. arvense (Joksic et al, 2003;Radulovic et al, 2006), S. tamariscina (Woo et al, 2005), A. capillus-veneris (Guha et al, 2004(Guha et al, , 2005Besharat et al, 2008), Athyrium pectinatum (Parihar et al, 2006), P. vittata (Singh et al, 2008b), P. multifida (Hu et al, 2008;Hum et al, 2008), Mecodium exsertum (Maridass, 2009), Selaginella involvens (Fig. 5g), S. inaequalifolia (Haripriya et al, 2010), S. pallescens (Rojas et al, 1999), Asplenium scolopendrium, Cystopteris fragilis, P. vulgare (Soare et al, 2012b), A. caudatum, A. evecta, Pteris confusa, P. argyraea, Lygodium microphyllum (Gracelin et al, 2012, Pteris biaurita (Dalli et al, 2007;de Britto et al, 2012), D. crassirhizoma (Lee et al, 2009), and various species (Maruzzella, 1961;McCutcheon et al, 1995). Furthermore, several studies (May, 1978;Dixit and Vohra, 1984;Dixit, 1992;Verma and Singh, 1995;Manandhar, 1996;Das, 1997;Singh, 1999;Benjamin and Manickam, 2007) have reported the antiviral, antibacterial, and antifungal activity of Equisetum ramosissimum (Fig.…”
Section: Antimicrobial Activitymentioning
confidence: 99%